Prinsip Etik dalam Al-Quran tentang Profesi Notaris di Indonesia - Saiful Munir; Hidayati, Rahmatul; Sunardi (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
The notary profession plays an important role in maintaining the credibility of notarial practice. The existence of Law No. 2 of 2014 concerning the Position of Notary has not yet been able to fully uphold this credibility, as in reality, issues related to improper recording practices in Indonesia often referred to as bogus records are still frequently encountered. This study aims to interpret notarial practice based on principles from the Qur'an, which emphasize the actualization of notaries as professionals. A qualitative-interpretative method was used, guiding the researcher to interpret the professional conduct of notaries. In conducting this interpretation, the researcher refers to QS. Al-Baqarah (2): 282, At-Taubah (9): 119, An-Nahl (16): 90, and Al-Ahzab (33): 72. The findings of this study indicate that Qur'anic values such as honesty (sidq), justice (‘adl), and trustworthiness (amānah) are essential in shaping the professional ethics of notaries. The implementation of these values can strengthen the integrity of the notary profession serving as a moral guideline in carrying out their duties not merely as an administrative obligation. This study proposes the need for integrating Qur'anic values into notary professional education and reinforcing ethical code supervision to create a more moral and civilized legal system.